A recombinant glucocorticoid‐induced leucine zipper protein ameliorates symptoms of dextran sulfate sodium‐induced colitis by improving intestinal permeability. Issue 11 (6th October 2021) - Gentili, Marco; Hidalgo‐Garcia, Laura; Vezza, Teresa; Ricci, Erika; Migliorati, Graziella; Rodriguez‐Nogales, Alba; Riccardi, Carlo; Galvez, Julio; Ronchetti, Simona
Abstract: Inflammatory bowel diseases (IBDs) are chronic inflammatory disorders characterized by relapsing intestinal inflammation, but many details of pathogenesis remain to be fully unraveled. Glucocorticoid (GC)‐induced leucine zipper (GILZ) is a mediator of the anti‐inflammatory effects of GCs, the most powerful drugs for IBD treatment, but they cause several unwanted side effects. The fusion protein TAT‐GILZ has been successfully used in some pre‐clinical models of inflammatory and autoimmune diseases. To test the efficacy of TAT‐GILZ for treating dextran sulfate sodium (DSS)‐induced colitis and explore its impact on the gut microbiome, colitis was induced by DSS in C57BL/6J mice and treated with TAT‐GILZ or dexamethasone. Various hallmarks of colitis were analyzed, including disease activity index, gut permeability, and expression of pro‐inflammatory cytokines and tight junction proteins. TAT‐GILZ treatment showed a therapeutic effect when administered after the onset of colitis. Its efficacy was associated with improved gut permeability, as evidenced by zonula occludens‐1 and CD74 upregulation in inflamed colonic tissue. TAT‐GILZ also ameliorated the changes in the gut microbiota induced by the DSS, thus potentially providing an optimal environment for colonization of the mucosa surface by beneficial bacteria. Overall, our results demonstrated for the first time that TAT‐GILZ treatment proved effective after disease onset allowing restoration of gut permeability, a key pathogenic feature of colitis. Additionally, TAT‐GILZ restored gut dysbiosis, thereby contributing to healing mechanisms. Interestingly, we found unprecedented effects of exogenous GILZ that did not overlap with those of GCs.